Immunohistochemical diagnosis of Caprine alphaherpesvirus 1 (CpHV-1) in Mexico - Llanos-Salinas, Samantha P.; Cobos-Marín, Laura; Candanosa-Aranda, Eugenia (Austral Journal of Veterinary Sciences, 2018)
The aim of this study was to identify the presence of Caprine alphaherpesvirus 1 (CpHV-1) in goat organs with suggestive injuries caused by the virus. A descriptive and retrospective study was performed, selecting necropsy cases suggestive of CpHV-1infection during a period of five years. Forty eight suspected cases were obtained, to which the immunohistochemistry technique with a CpHV-1 monoclonal antibody, was applied. We observed positivity in 24 goatling cases under 15 days (50%) and in 4 cases of adult animals (8.3%). The presence of CpHV-1 in goats from the Mexican plateau is confirmed.